2018
DOI: 10.1159/000494794
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape of Non-Coding RNA in an Adult Pig Model of Intrauterine Growth Restriction

Abstract: Background/Aims: Intrauterine growth restriction (IUGR) is a risk factor for adult metabolic syndrome, but how this disease is regulated by lncRNAs and circRNAs remains elusive. Methods: Here, we employed adult IUGR and normal pigs as models to evaluate the expression of various global lncRNAs and circRNAs in pig livers using RNA-seq. Results: In total, we obtained 1,162 million raw reads of approximately 104.54 Gb high quality data. After a strict five-step filtering process, 3,368 lncRNAs were identified, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Accumulating evidence supports that circRNAs are important biological molecules associated with disease pathogenesis (Kristensen et al, 2019;Yu et al, 2019). Shen et al (2018) identified 44 differentially expressed circRNAs in pig livers using adult IUGR and normal pigs as models, via RNA sequencing. They identified ATF4/miR-214/circRNA7964 and TCF7/miR-22-3p/circRNA16347 as two competing endogenous networks by bioinformatic analysis (Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence supports that circRNAs are important biological molecules associated with disease pathogenesis (Kristensen et al, 2019;Yu et al, 2019). Shen et al (2018) identified 44 differentially expressed circRNAs in pig livers using adult IUGR and normal pigs as models, via RNA sequencing. They identified ATF4/miR-214/circRNA7964 and TCF7/miR-22-3p/circRNA16347 as two competing endogenous networks by bioinformatic analysis (Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al (2018) identified 44 differentially expressed circRNAs in pig livers using adult IUGR and normal pigs as models, via RNA sequencing. They identified ATF4/miR-214/circRNA7964 and TCF7/miR-22-3p/circRNA16347 as two competing endogenous networks by bioinformatic analysis (Shen et al, 2018). In addition, circPAPPA and circTRNC18 play regulatory roles in trophoblast cells (Shen et al, 2019;Zhou et al, 2019) and a subset of placental cells, thus performing critical functions in fetal growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study found that LBW-induced changes in methylation in the intestine were mainly involved in biological processes, such as cell apoptosis and cell differentiation, suggesting that LBW piglets have a higher incidence of intestinal dysfunction (24). The adverse effects of LBW on fetuses and newborns may persist throughout the life cycle (25,26). Recent studies have shown that LBW young adults have a higher incidence of short-and long-term dysfunction in several vital organs (27)(28)(29); however, the effect of LBW on the intestinal barrier function of young adults is still not well characterized.…”
mentioning
confidence: 99%
“…According to our previous study [59], total RNA was extracted from PMM and LDM using TRIZOL (Invitrogen, Carlsbad, CA, USA), and further purified with RNeasy column (Qiagen, Valencia, CA, USA) according to the manufacturer’s protocol. Total DNA was isolated from LDM and PMM for the measurement of mtDNA copy number by using the DNeasy Blood & Tissue Kit (Qiagen, USA).…”
Section: Methodsmentioning
confidence: 99%
“…As in our previous study [59], the clean data were obtained by removing reads containing adapters, reads containing over 10 % of poly (N), and low-quality reads (>50 % of the bases had Phred quality scores ≤ 10) from the raw data. All the downstream analyses were based on high quality clean data.…”
Section: Methodsmentioning
confidence: 99%